Integrating economic and environmental impact analysis: the case of rice-based farming in northern Thailand - Ramsden, Stephen J.; Wilson, Paul; Phrommarat, B. (Elsevier, 2017)
Crop production is associated with a range of potential environmental impacts, including field 9 emissions of greenhouse gases, loss of nitrogen and phosphorous nutrients to water and toxicity 10 effects on humans and natural ecosystems. Farmers can mitigate these environmental impacts 11 by changing their farming systems; however these changes have implications for production 12 and profitability. To address these trade-offs, a farm-level model was constructed to capture 13 the elements of a rice-based production system in northern Thailand. Life Cycle Assessment 14 (LCA) was used to generate environmental impacts, across a range of indicators, for all crops 15 and associated production processes in the model. A baseline, profit maximising combination 16 of crops and resource use was generated and compared with a greenhouse gas minimising 17 scenario and an alternative inputs (fertilisers and insecticides) scenario. Greenhouse gas 18 minimisation showed a reduction in global warming potential of 13%; other impact indicators 19 also decreased. Associated profit foregone was 10% as measured by total gross margin. With 20 the alternative farm inputs (ammonium sulphate, organic fertiliser and fipronil insecticide), 21 results indicated that acidification, eutrophication, freshwater and terrestrial ecotoxicity 22 impacts were reduced by 43, 37, 47 and 91% respectively with relatively small effects on profit.